2015
DOI: 10.1007/s11916-015-0511-2
|View full text |Cite
|
Sign up to set email alerts
|

SUNCT/SUNA: A Review

Abstract: Short-lasting unilateral neuralgiform headache attacks with conjunctival injection and tearing (SUNCT) and short-lasting neuralgiform headache attacks with cranial autonomic features (SUNA) are rare headache disorders characterized by severe, short-lasting headaches. These headache disorders are often refractory to treatment and can be secondary phenomena. This article reviews the history, pathophysiology, and treatment of these disorders. Both pharmacotherapy and procedural interventions are discussed in cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 35 publications
(49 reference statements)
0
27
0
1
Order By: Relevance
“…Recent studies have reported satisfactory results using antiepileptic drugs; currently, the first-line agent is lamotrigine, whereas the second-line drugs include gabapentin and topiramate. [4,5] For severe and treatment-resistant patients, there are pioneer studies on deep brain stimulation and microvascular surgery. [6][7][8][9] Some authors have reported conflicting results regarding the efficacy of great occipital nerve (GON) block.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported satisfactory results using antiepileptic drugs; currently, the first-line agent is lamotrigine, whereas the second-line drugs include gabapentin and topiramate. [4,5] For severe and treatment-resistant patients, there are pioneer studies on deep brain stimulation and microvascular surgery. [6][7][8][9] Some authors have reported conflicting results regarding the efficacy of great occipital nerve (GON) block.…”
Section: Discussionmentioning
confidence: 99%
“…In addition there are positive reports on topiramate, carbamazepine, gabapanetin, botulinum toxin, and nerve blocks, which seemed to be effective in some patients . Invasive procedures used in patients refractory to pharmacological treatment include microvascular decompression, deep brain stimulation, and occipital nerve stimulation . In two small case series, microvascular decompression rendered seven of 12 patients pain‐free.…”
Section: Sunct/sunamentioning
confidence: 99%
“…In two small case series, microvascular decompression rendered seven of 12 patients pain‐free. Apart from lack of efficacy, the procedure may cause serious adverse effects such as hearing loss and dysequlibrium . In 11 patients, deep brain stimulation of the ventral tegmental area showed a 50% improvement in daily attack frequency in 82% of the patients and a reduction in headache load by 99%.…”
Section: Sunct/sunamentioning
confidence: 99%
See 2 more Smart Citations